The Women’s Languages Used by Taylor Swift in Miss Americana Documentary Film - Dewi, Viana Mulya; Parthama, I Gusti Ngurah; Mulyana, Novita (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2026)
This study is entitled The Women’s Languages Used by Taylor Swift in Miss Americana Documentary Film. The study of sociolinguistics found that there are differences in how men and women speak. Holmes (2013) stated that women tend to speak in a more standard form of English. Based on the differences found in the way women and men speak, this study aimed to find the types of women’s language features and function in Taylor Swift’s utterances. Women’s language features proposed by Lakoff (1975) and women’s language function proposed by Pearson (1985) were applied in this study. The data of this study was taken from Miss Americana documentary film. The data source was taken from Taylor Swift’s utterances in the form of transcript of the film that was taken from the website. Qualitative method, particularly descriptive was used in this study. Based on 140 utterances, seven of them were analyzed. It was found that seven out of ten women’s language features were used by Taylor Swift. They were lexical hedges or fillers, rising intonation on declaratives, intensifiers, hypercorrect grammar, super polite forms, avoidance of strong swear words, and emphatic stress. Out of all features found, lexical hedges or fillers were the most frequently features used by Taylor Swift. Rising intonation on declaratives were the least ones used by Taylor Swift in the documentary Miss Americana. Four out of five function was found in her utterances. Lexical hedges were aimed to start a discussion. They were to get response, to express feeling to soften an utterance. Meanwhile, the women language’s feature fillers are function only as breath gap filler. Keywords: Women’s languages feature, Women’s languages function, Documentary film